Hubungan Quadriceps Angle dengan Knee Osteoarthritis di Panti Sosial Harapan Kita - juliastuti, juliastuti juliastuti (Masker Medika, 2020)
Introduction: Osteoarthritis is a condition of joint crises and articular cartilage damage due to osteophyte, pain, restricted movement and deformity. Osteoarthritis plays an important role as a major cause of pain and disability in the elderly. Methods: The study was conducted with a quantitative approach, including in analytical research. This type of research is a non-experimental study using Pearson test and One Way Anova by presenting the results of measuring the Q-angle angle using a Goniometer from measurement of knee function using KOOS (Injury and Osteoarthritis Score Questionnaire). Result: there is a linear relationship between the Koos Score and the Q Angle, the Pearson correlation coefficient or R value between variables is 0.868, which means that the two variables have a positive or straight proportional relationship and are very strong. Discussion: The results of this study, it can be seen that there is a positive relationship between knee function and the magnitude of the Quadriceps angle in cases of knee osteoarthritis and it can show that the greater the Q angle, the higher the knee functionality score.